Odpowiedzi

2010-01-14T14:17:39+01:00
A)
6x-7(11+2x)+2=-4(15-x)+3
6x-77-14x+2=-60+4x+3
6x-14x-4x=-60+3+77-2
-12x=132|:(-12)
x=-11

b)
3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x-7x-3x=35-6-9
5x=20|:5
x=4

c)
2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x+6+9x
2x+4x+3x-9x=6+2+12
0≠20 sprzeczne

d)
5x-3(6-8x)=x-7(x+4)
5x-18+24x=x-7x-28
5x+24x-x+7x=-28+18
35x=-10|:35
x=-2/7
2010-01-14T14:24:06+01:00
A)6x-7+11+2x+2=-4+15-x+3
7x=7-11-4+15+3
7x=21
x=21:7
x=3

b)3+5x+3=7+x+5-3+2-x
5x-x+x=-3-3+7+5-3+2
5x=5:5
x=5

c)5x-3+6-8x=x-7+x+4
5x-8x-x=3-6-7+4
-4x=-6
x=4:6
x=1 1/2 (jeden i jedna druga)
2010-01-14T14:35:45+01:00
A) 6x-7(11+2x)+2=-4(15-x)+3
6x-77-14xplus2=-57 plus4xplus3
-8x-75=-56plus4x
-8x-4x=75-57
-12x=18
x=- 18/12

b)3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x-7x-3x=-9+35-6
5x= 20
x=4
c) 2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x+6+9x
2x+4x+3x-9x=2+12+6
0nie równa się 20
d) 5x-3(6-8x)=x-7(x+4)
5x-18+24x= x-7x-28
5x+24x+7x-x=18-28
35x=-10
x= -10/35